Using Coaching to Support Experiential Learning in Global Virtual Teams (GVTs) – Interrogating Perceptions of Impact. - Gilbertson, Deb; Cathro, Virginia; Mail, Morne; Mail, Anelda (Journal of University Teaching and Learning Practice, 2024)
In 2021, recognising the perceived strengths and risks, along with the tumult experienced by students in a COVID-19 university context, a coaching program was wrapped around the Global Enterprise Experience (GEE) to support student learning. This program involved the training, development and support of a 59 strong volunteer coach team. This paper reports the experiences of these coaches and the perceived impact of the coaching program from the perspective of coaches. At the conclusion of the GEE contest, coaches participated in a debriefing interview comprising open-ended questioning. Each coach was asked the same question set pertaining to their sense of did they have impact? Narrative responses were transcribed, collated within NVivo and analysed using thematic analysis and concept mapping techniques (Braun & Clarke, 2006; Terry et al., 2017). Clear emergent themes support the coaches’ belief that they had impact upon student learning. Impact was described in numerous ways. That the program was valuable to coaches and team leaders alike is noteworthy. Most especially that as an offering the program has impact and is scalable and sustainable. This finding is noteworthy as scalability and sustainability in the mix of offering students support within experiential learning contexts are tipping points. It also offers qualitative support for coaching program impact, revealing the unanticipated positive experiences of the coaches themselves suggesting a potent sustainability factor. This study contributes to understanding of coaching undergraduates engaging in experiential GVT coaches and with practical implications of structuring support.